The Effectiveness of Vertical Jump Training on Volleyball Spiking Performance - Kenangan Tektrisman Zega; Bela Sintiya; Bayu Tio Jahtra Gurusinga; Cina Pakpahan; Ervan Mario Gomos Tanjung; Jidan Christian Sianipar; Randi Kurniawan; Deni Rahman Marpaung (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study examined the effectiveness of vertical jump training on volleyball spiking performance through a literature review of several peer-reviewed journal articles published in the past decade. previous research indicated that vertical jump height played a critical role in determining a player’s ability to generate optimal spiking power, reach, and ballcontact angle. the purpose of this study was to synthesize empirical findings on how vertical jump ability contributed to improvements in spiking performance and to identify the types of training interventions most effective for enhancing jump capacity. the review method involved selecting reputable journals focusing on volleyball performance, strength and conditioning, biomechanics, and sports training, followed by screening articles that specifically discussed vertical jump measurements, plyometric training programs, and spike-related performance outcomes. the results showed that athletes who engaged in structured vertical jump trainingparticularly plyometric drills, lower-body strength training, and neuromuscular conditioningconsistently demonstrated increased jump height, enhanced explosive power, and improved spike velocity and accuracy. several studies also reported that improved vertical jump ability positively influenced approach speed, timing, and overall offensive effectiveness during matches. the review concluded that vertical jump training was an effective performance-enhancement strategy for volleyball players, -especially hitters, and served as an essential component of modern volleyball conditioning programs. the implications of this study emphasized the importance of integrating progressive plyometric and strength-based interventions into regular training schedules to maximize athletes’ spiking performance and reduce the risk of injury associated with inadequate jump mechanics.keywords: vertical jump, spiking performance, volleyball training, plyometric exercise, explosive power